Combined Treatment with PPAR-γ Agonists in Pancreatic Cancer: A Glimmer of Hope for Cancer Therapy? - Dicitore, Alessandra; Caraglia, Michele; Colao, Annamaria; Zappavigna, Silvia; Mari, Daniela; Hofland, Leo J.; Persani, Luca; Vitale, Giovanni (Current Cancer Drug Targets, 2013)
Pancreas cancer is the fourth leading cause of cancer death due to the limited treatment success rate. The wide number of signalling pathway aberrations contributing to tumorigenesis, progression and drug resistance, is the main reason for unsuccessful treatments in pancreatic cancer. An additional and still under-investigated intracellular cancer target is the peroxisome proliferator activated receptor gamma (PPAR-γ). Several studies have shown the in vitro antitumor activity of PPAR-γ agonists in cancer cells but, if used in monotherapy, they were poorly effective in cancer treatment. The present review will focus on the potential therapeutic role of PPAR-γ agonists in combination with other drugs (type I interferons, gemcitabine and COX-2 inhibitors), highlighting molecular interactions and signalling pathways involved in pancreatic cancer cells. Understanding of the underlying molecular mechanisms and survival pathways activated in cancer cells should promote the development of more successful strategies based on the specific targeting of molecular pathways involved in the resistance to anti-cancer agents.
Keywords: pancreatic cancer